'A New Order is Being Created': Domestic Modernism in 1930s Britain. Issue 3 (November 2016) - Moore, Daniel
Abstract : This article addresses the attempts in Britain in the 1930s to integrate modernist aesthetics with the home. A number of initiatives during this period were directed towards improving both standards of living and the public's taste: arising from exposure to continental modernism (Adolf Loos, Le Corbusier) and with a fervent belief in the democratisation of the living space, innovators such as Wells Coates, Jack and Molly Pritchard, and Maxwell Fry sought to re-invent the home for the twentieth century. The results were often short-lived, and in some cases, abject failures. Yet the negotiations that these designers, architects, and visionaries made between high-minded aesthetics and the practicalities of quotidian British life reveal much about standards of taste during the 1930s. This article takes two case studies in detail: The Lawn Road Flats – the Isokon Building – in Hampstead, London, and the activities of the Design and Industries Association (DIA). In doing so, I chart the ways in which interior design developed in Britain during the decade before the outbreak of World War Two, and explore how small-scale, short-lived activities in this period laid the foundations for a flowering of new modes of living post-1945.